Influence of standard load micro and nanopatterned in surface roughness of bleached teeth and submitted to different surface treatments? - Nacanichi, Renata do Amaral; Tonetto, Mateus Rodrigues; Bandéca, Matheus Coelho; Andrade, Marcelo Ferrarezi de [UNESP]; Segalla, José Cláudio Martins [UNESP]; Silva, Monica Barros; Bhandi, Shilpa H.; Pedro, Fábio Luiz Miranda; Elossais, André Afif (Jaypee Brothers Medical Publishing, 2014)
The aim of this study was evaluate the dental enamel after whitening treatment with Opalescence Boost PF® 38%, correlating the structural alterations in the surface of the enamel with its respective pH and verify if whitened teeth submitted to different finishing and polishing techniques show similar surface texture to healthy teeth (control group). Sixty premolars were divided in 6 groups (n = 10), which had been immersed in artificial saliva during all the experiment. Protocol whitening was performed according to the manufacturer recommendations, and then the specimens were submitted to different polishing technique with Sof-Lex Pop On® disks, Flex Diamond® felt disks using two different micrometric polishing pastes (Enamelize® and Diamond Polish®) and two nanometric polishing pastes (Lummina-E Diamond and Lummina-E Alumina), according to the groups. Representative specimens were analyzed in scanning electronic microscopy (SEM). Whitening gel used in this experiment had modified the morphologic aspect of the enamel surface. It was found that two nanometric polishing pastes (G5 and G6) promoted a less rough surface compared to control group even after the whitening process.
Keywords: Dental enamel; Bleaching; Surface properties; Polishing